Neoliberals in Latin America.Ortodox and conventional (2014)
In Latin America the neoliberalism began earlier and has faced greater resistance. It is a reactionary practice, conservative thinking and accumulation model based on attacks to workers, in a context of greater internationalization of the capital. There was an initial stage of adjustment and another phase of privatizations during the dictatorships and the subsequent transitions.